2014
DOI: 10.1093/mnras/stu309
|View full text |Cite
|
Sign up to set email alerts
|

A new HCN maser in IRAS 15082−4808

Abstract: We have identified a new vibrational HCN maser at 89.087 GHz in the asymptotic giant branch (AGB) star IRAS 15082−4808, a maser which is thought to trace the innermost region of an AGB envelope. The observations of this maser at three epochs are presented: two positive detections and one null detection. The line profile has varied between the positive detections, as has the intensity of the maser. The major component of the maser is found to be offset by −2.0 ± 0.9 km/s with respect to the systemic velocity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…The most unusual detection made is that of the vibrational (v2=2) HCN maser emission at 89.087 GHz. Only ten of these masers, including this detection, have been found to date (Smith et al 2014;Lucas et al 1986;Guilloteau et al 1987;Lucas et al 1988;Lucas & Cernicharo 1989). An in-depth study of this maser can be found in Smith et al (2014) and the maser line is shown in Fig.…”
Section: Iras 15082-4808mentioning
confidence: 71%
See 4 more Smart Citations
“…The most unusual detection made is that of the vibrational (v2=2) HCN maser emission at 89.087 GHz. Only ten of these masers, including this detection, have been found to date (Smith et al 2014;Lucas et al 1986;Guilloteau et al 1987;Lucas et al 1988;Lucas & Cernicharo 1989). An in-depth study of this maser can be found in Smith et al (2014) and the maser line is shown in Fig.…”
Section: Iras 15082-4808mentioning
confidence: 71%
“…This line, as shown in Smith et al (2014), can be well modelled by a blend of the three hyperfine components, each having a Gaussian velocity distribution. The hyperfine structure lines in C4H are blended, with their relative intensities impossible to determine from the observed blended transition.…”
Section: Iras 15194-5115mentioning
confidence: 90%
See 3 more Smart Citations